PROBLEMS AND PROSPECTS OF ESTABLISHMENT OF THE MAXIMUM WAGES IN RUSSIA - V. Ostapenko (Вестник университета, 2018)
In the article theoretical developments on problems of legislative establishment of the maximum wages as tool of a state income policy have been generalized. The analy-sis of foreign experience of definition by the state of the top limit of a wages in the condi-tions of the increasing gap in CEO and worker pay has been carried out. The conclusions have been drawn on a possibility of application of restrictive measures of a wages in Rus-sian economy as way of decrease of income inequality of the population.